1932
DOI: 10.1177/003591573202500801
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Induced Malignant Tertian Malaria

Abstract: Introduction.-Justification for employing P. falciparum in the practice of malariatherapy. (II) Origin of the strains of P. falciparum used.-Eight strains of the parasite were used, of which two were from India, three from Rome, one from Sardinia and two from West Africa. The manner in which the strains were obtained is described and a list of cases infected with them, some by blood inoculation, others by the bites of mosquitoes, is given. (III) Problems of morphology and of biological properties.-Two problems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
2

Year Published

1934
1934
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 2 publications
1
33
0
2
Order By: Relevance
“…In 1932, James and coworkers stated that it was unlikely that another malignant species besides P. falciparum would be discovered [39]. Since then Plasmodium knowlesi was found to be infective for humans leading to life-threatening quotidian malaria.…”
Section: Discussionmentioning
confidence: 99%
“…In 1932, James and coworkers stated that it was unlikely that another malignant species besides P. falciparum would be discovered [39]. Since then Plasmodium knowlesi was found to be infective for humans leading to life-threatening quotidian malaria.…”
Section: Discussionmentioning
confidence: 99%
“…The notion that P. falciparum parasites differ in the clinical manifestations they provoke is not new. From their observations of induced mild malaria infections, James et al [11] concluded in 1932 that "A striking difference can be observed between the clinical virulence of different geographical races or strains of the same morphological species of the parasite; the difference is particularly apparent between various races of P. falciparum" (page 1176). Strain-specific infection patterns were observed in experimental infection of Saimiri monkeys [12].…”
Section: Discussionmentioning
confidence: 99%
“…Since merozoite surface protein-1 has a key role in invasion of red blood cells, it is conceivable that specific msp-1 allelic forms favor more efficient invasion than do others. A rapid multiplication rate allows parasites to reach a high density before an effective protective response is established and, as such, contributes to severity [1,11,15].…”
Section: Discussionmentioning
confidence: 99%
“…P. vivax is more transmissible: producing gametocytes straight out of the liver, yielding a higher number of sporozoites per oocyst, and, of course, the production of hypnozoites which allow the parasite to remain dormant and relapse. In addition, P. vivax appears able to infect a wide range of mosquito vectors in different geographical areas (Boyd and Kitchen 1936;Collins et al 1976: 372-5;Daskova and Rasnicyn 1982: 893-7) and does not seem to suffer from vector incompatibilities as is documented with P. falciparum (Daskova and Rasnicyn 1982: 893-7;James et al 1932James et al : 1153Ramsdale and Coluzzi 1975: 39-48). These adaptations imply that P. vivax is more adapted for surviving in Downloaded by [Baskent Universitesi] at 09:42 20 December 2014 environments that are less conducive for transmission, and it is therefore reasonable to suggest that P. vivax has a longer association with humans than P. falciparum .…”
Section: Historical Records Of Human Malariamentioning
confidence: 96%